2018
DOI: 10.1001/jamadermatol.2018.1628
|View full text |Cite
|
Sign up to set email alerts
|

Cutavirus Infection in Primary Cutaneous B- and T-Cell Lymphoma

Abstract: Drs Halpern and Gonzalez reported having served on the scientific advisory board of Caliber Imaging and Diagnostics. No other disclosures were reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 5 publications
4
17
0
Order By: Relevance
“…CuV has already gained much interest due to its association with cutaneous T-cell lymphoma, despite being discovered only in 2016. It has been predominantly searched for in skin cancers [ 4 , 20 , 21 , 22 ], however, nothing is known of its acute infections. No respiratory or stool samples have been analyzed for its prevalence or to characterize its possible symptoms in acute infections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CuV has already gained much interest due to its association with cutaneous T-cell lymphoma, despite being discovered only in 2016. It has been predominantly searched for in skin cancers [ 4 , 20 , 21 , 22 ], however, nothing is known of its acute infections. No respiratory or stool samples have been analyzed for its prevalence or to characterize its possible symptoms in acute infections.…”
Section: Discussionmentioning
confidence: 99%
“…CuV has been more widely studied in skin samples than in stool or respiratory samples. So far, CuV DNA has been detected in skin biopsies of CTCL, melanoma and transplant patients with prevalences between 1.1–16% [ 4 , 21 , 22 , 23 ], but not in those of healthy subjects [ 4 , 21 ]. However, viral DNA has surprisingly been found in skin surface swabs of healthy adults (9/237, 3.8%) and of HIV-positive men (35/205, 17.1%) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phan et al have found cutavirus DNA in 23.5% (4/17) ( 1 ) and Väisänen et al in 16% (4/25) of CTCL of the mycosis fungoides type ( 5 ). Our group recently analyzed 189 biopsies of various cutaneous B- and T-cell lymphoma types and detected cutavirus DNA only in 5.8% of 104 mycosis fungoides biopsy specimens ( 7 ). In contrast, Bergallo et al could not detect cutavirus in 55 CTCL samples ( 8 ).…”
mentioning
confidence: 99%
“…In 2016, CuV was found in human fecal samples and cutaneous T-cell lymphomas (CTCL) [5,11]. While CuV DNA was found in skin biopsies from~5% of German and 16% of Finnish patients with CTCL [16,17], it was absent in healthy patients, providing a statistically significant association to CTCL [17]. It has been infrequently detected also in malignant skin melanomas and carcinomas [11,17,18].…”
Section: Introductionmentioning
confidence: 99%